Implementation of The Case Study Project Approach in The Development of Multicultural Education Textbooks to Improve Critical Thinking Skills - Muhammad Yusuf Ritonga; Mukhlis Lubis; Salman Alparis Sormin; Dharma Gyta Sari Harahap; Siti Meutia Sari (Fakultas Keguruan dan Ilmu Pendidikan, ULM, 2025)
This study aims to develop a Multicultural Education textbook based on the Case Study Project (CSP) approach to improve the critical thinking skills of History Education students. The research employed a Research and Development method using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The study involved 68 students from the History Education Program at a university in Indonesia. The research instruments consisted of validation sheets, response questionnaires, and critical thinking skill tests. Data were analyzed through validity tests, practicality tests, and effectiveness tests using a paired sample t-test. The results indicate that the developed textbook demonstrates high validity (average score 89.5%), excellent practicality (average score 87.3%), and effectively improves students’ critical thinking skills with a significance value of p < 0.05. The improvement was evident in analytical, evaluative, and synthetic skills across diverse cultural perspectives. Therefore, the textbook is feasible for use as an alternative learning resource in Multicultural Education and represents an instructional innovation relevant to fostering 21st-century competencies in higher education.